2018
DOI: 10.1542/peds.2017-1630
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Improvement of Pediatric Asthma Guideline Improves Hospital-Based Care

Abstract: The hospital-wide standardization of a pediatric asthma CPG across hospital units can safely reduce overall hospital resource intensity by reducing LOS, admissions, ICU services, and charges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 23 publications
(32 reference statements)
0
33
0
Order By: Relevance
“…Thus, there is a need to identify implementation strategies that can help promote guidelines or protocols targeted towards this subpopulation in emergency settings. There is evidence that the quality of care in pediatric emergencies has improved with the implementation of evidence-based guidelines in the emergency management of children [4,5]. To continue this trend, and implement it in other areas of care, we first must identify successful implementation strategies and identify patterns of success among these strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a need to identify implementation strategies that can help promote guidelines or protocols targeted towards this subpopulation in emergency settings. There is evidence that the quality of care in pediatric emergencies has improved with the implementation of evidence-based guidelines in the emergency management of children [4,5]. To continue this trend, and implement it in other areas of care, we first must identify successful implementation strategies and identify patterns of success among these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…While some recent studies examining the effect of implementing guidelines in emergency management of children have found positive outcomes [4,5,9], others have reported no significant effects on the outcomes [10]. It is unclear if this is a result of poor implementation strategies or lack of reporting on what entailed the implementation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need to identify implementation strategies that can help promote guidelines or protocols targeted towards this subpopulation in emergency settings. There is evidence that the quality of care in pediatric emergencies has improved with the implementation of evidence-based guidelines in pediatric emergency management (PEM) [4,5]. To continue this trend, and implement it in other areas of care, we first must identify successful implementation strategies and identify patterns of success among these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…While some recent studies examining the effect of implementing PEM guidelines have found positive outcomes [4,5,9], others have reported no significant effects on the outcomes [10]. It is unclear if this is a result of poor implementation strategies, or lack of reporting on what entailed the implementation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need to identify implementation strategies that can help promote guidelines or protocols targeted towards this subpopulation in emergency settings. There is evidence that the quality of care in pediatric emergencies has improved with the implementation of evidence-based guidelines in emergency management of children [4,5]. To continue this trend, and implement it in other areas of care, we first must identify successful implementation strategies and identify patterns of success among these strategies.…”
mentioning
confidence: 99%